2006
DOI: 10.1158/1078-0432.ccr-05-2489
|View full text |Cite
|
Sign up to set email alerts
|

Captopril, an Angiotensin-Converting Enzyme Inhibitor, Promotes Growth of Immunogenic Tumors in Mice

Abstract: Purpose: Antitumor potential of angiotensin-converting enzyme inhibitors has been shown in different preclinical settings, which always involved immunocompromised organisms or nonimmunogenic tumor models. In our study, we wanted to evaluate the effect of captopril on growth of immunogenic tumors in immunocompetent animals. Experimental Design: We used different murine tumor models to evaluate the effect of captopril on tumor take and survival of tumor-bearing immunocompetent and immunocompromised mice. We used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 42 publications
3
17
0
3
Order By: Relevance
“…However, a few reports have suggested that ACEis may actually promote tumor growth, possibly due to their immunomodulatory activity, 139 and patients treated with ACEis have been reported to have higher rates of kidney cancers. 140 However, several other clinical studies have shown that ACEis do not increase the risk of cancer.…”
Section: Anticancer Effect Of Aceismentioning
confidence: 99%
“…However, a few reports have suggested that ACEis may actually promote tumor growth, possibly due to their immunomodulatory activity, 139 and patients treated with ACEis have been reported to have higher rates of kidney cancers. 140 However, several other clinical studies have shown that ACEis do not increase the risk of cancer.…”
Section: Anticancer Effect Of Aceismentioning
confidence: 99%
“…17,18 Other orthotopic tumor models such as prostate or colorectal cancer have also underlined the importance and specificity of an organ-specific microenvironment on tumor biology. 19,20 We have analyzed the efficacy of RENCA-H6 vaccine in various settings resembling particular clinical conditions observed in RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Właściwość tę wykazano w badaniach z wykorzystaniem Captoprilu -inhibitora konwertazy angiotensyny, który jest powszechnie stosowany w leczeniu nadciśnienia. Pomimo swoich właściwości przeciwnowotworowych w badaniach przedklinicznych wykazano wpływ Captoprilu na promocję wzrostu guzów immunogennych (takich jak RCC) poprzez osłabienie przeciwnowotworowej odpowiedzi układu immunologicznego, mimo braku ogólnoustrojowych efektów immunosupresji [7,27].…”
Section: Wiktoria Maria Suchorska Mikołaj Nowak / Zeszyty Naukowe Wcunclassified